Malting barley response to integrated organic and mineral nutrient sources in Nitisol - Kassu Tadesse; Asrat Mekonnen; Almaz Admasu; Wubengda Admasu; Dawit Habte; Amare Tadesse; Bahiru Tilahun (International Journal of Recycling of Organic Waste in Agriculture, 2018)
Abstract Purpose Depletion of soil fertility accounts for the low yield and quality of malting barley (Hordeum vulgare) in Ethiopia. Mineral fertilizers can counteract nutrient depletion but are unaffordable by low-input farmers. Organic amendments can contribute to correct soil degradation but are often unavailable in the required amounts. Therefore, this experiment was conducted to investigate the effects of combined use of organic and mineral amendments on the yield and quality of malting barley, and on selected soil chemical properties at Lemu-Bilbilo district in the southeastern highlands of Ethiopia. Methods Eight treatments were arranged in randomized complete block design with three replications to compare sole and integrated applications of organic and mineral nutrient sources on crop performance attributes and selected soil characteristics. Results Application of 2.82 t ha−1 compost or 1.07 t ha−1 farmyard manure (FYM) along with 18–10 kg ha−1 N–P gave 4234–4443 kg ha−1 grain yield with 15–17 and 32–39% increase over sole organic amendments and control, respectively, and 757% economic benefit. Combining organic and mineral fertilizers also gave 7–17 and 1–6% increase in available soil P and total N content of the soil. Conclusion Combined application of 50% recommended compost (RC) or 50% recommended FYM (RFYM) + 50% recommended NP (RNP) or 33% RC + 33% RFYM + 33% RNP enhanced yield, grain quality, soil attributes and economic benefits. Therefore, integration of organic and mineral amendments is recommended as best agronomic and economic optimum soil fertility management options for sustainable malting barley production in the southeastern highlands of Ethiopia.